Pigmentation pattern formation in butterfly wigns: Global patterns on fore- and hind-wing - Sekimura, T; Madzvamuse, A; Maini, P (Birkhauser, 2007)
Pigmentation patterns in butterfly wings are one of the most spectacular & vivid examples of pattern formation in biology. In this chapter, we devote our attention to the mechanisms for generating global patterns. We focus on the relationship between pattern forming mechanisms for the fore- and hindwing patterns. Through mathematical modeling and computational analysis of Papilio dardanus and polytes, our results indicate that the patterns formed on the forewing need not correlate to those of the hindwing in the sense that the formation mechanism is the same for both patterns. The independence of pattern formation mechanisms means that the coordination of unified patterns of fore- and hindwings is accidental. This is remarkable, because from Oudeman's principle [10], patterns appearing on the exposed surface of fore-and hindwing at the natural resting position are often integrated to form a composite and unified adaptive pattern with their surrounding environment.